To enhance the performance of all-inorganic perovskite photodetectors via constructing both bilayer heterostructure and bipolar carrier transporting channels. Issue 47 (15th November 2019) - Hu, Jinming; Shi, Yuansheng; Zhang, Zhenheng; Zhi, Ruonan; Li, Hailong; Tang, Yi; Yang, Shengyi; Zou, Bingsuo
Abstract : To enhance the device performance of all-inorganic perovskite photodetectors via constructing both bilayer heterostructure and bipolar carrier transporting channels. Abstract : Due to their intrinsic properties of ultrahigh carrier mobility and large absorption coefficients, inorganic halide perovskites (IHPs) have gained significant attention recently and have become one of the most competitive and promising candidates for optoelectronic devices. However, owing to large quantities of trap states on surfaces and grain boundaries, solution self-assembly IHP films suffer from low carrier-extraction and transport efficiencies. Therefore, in this paper, bilayer heterostructure photodetectors Au/[CsPbBr3 :ZnO/MoO3 ]/Au, in which bipolar carrier transporting channels were built, are firstly presented. Under 72.1 μW cm −2 405 nm illumination at 10 V, for the photodetector Au/[CsPbBr3 :ZnO/MoO3 ]/Au with an optimal precursor molar ratio (CsBr to PbBr2 ) of 1 : 1.2, an external quantum efficiency of 2304% with a responsivity of 7.53 A W −1 was obtained. Moreover, an enhanced ON/OFF ratio of >8 × 10 3 with a high specific detectivity of 5.22 × 10 13 Jones was also achieved. Therefore, such an approach of combining a bilayer heterostructure and bipolar transporting channels into one device provides a fairly promising method for high-performance all-inorganic perovskite-based photodetectors and other optoelectronic devices.